2019
DOI: 10.1021/acsapm.9b00246
|View full text |Cite
|
Sign up to set email alerts
|

Highly Flexible Mechanical Energy Harvester Based on Nylon 11 Ferroelectric Nanocomposites

Abstract: We report here a flexible piezoelectric energy harvester using castor-oil-derived nylon 11 and biomass-derived cellulose nanocrystals (CNC). Using a simple solution casting process, we were able to fabricate flexible large area nylon 11 and composite films. Neat nylon 11 films crystallized predominantly in the α- phase. Incorporation of CNC at a low concentration of 2–5 wt % resulted in almost complete transition of α-phase to polar γ-phase, which could be attributed to strong hydrogen bonding interactions bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 40 publications
2
22
0
Order By: Relevance
“…9 For instance, a-phase PA11 with tight crystalline packing and strongly bonded hydrogenbonding sheets which prevent dipole rotation is non-polarizable and therefore undesired. 14 Literature agrees on the fact that piezoelectricity of PA11 appears in g and d 0 -phase 15,16 while ferroelectricity can be exhibited by only d 0 -phase. 17 The d 0 phase is composed of a hydrogen-bonded network instead of hydrogen-bonding sheets, and molecular chain has a "twisted" conformation with weak hydrogen bonds and increased interchain distance in the crystal.…”
Section: Introductionsupporting
confidence: 53%
“…9 For instance, a-phase PA11 with tight crystalline packing and strongly bonded hydrogenbonding sheets which prevent dipole rotation is non-polarizable and therefore undesired. 14 Literature agrees on the fact that piezoelectricity of PA11 appears in g and d 0 -phase 15,16 while ferroelectricity can be exhibited by only d 0 -phase. 17 The d 0 phase is composed of a hydrogen-bonded network instead of hydrogen-bonding sheets, and molecular chain has a "twisted" conformation with weak hydrogen bonds and increased interchain distance in the crystal.…”
Section: Introductionsupporting
confidence: 53%
“…8(1) and ( 3)), which are highly exible, lightweight and sensitive to small vibrations, as well as mechanical stretching and annealing to increase the dipoles orientation and the degree of crystallinity of the piezoelectric crystalline phase of PA. 104,124 Another method reported in literature to improve the piezoelectric properties of PA11, is the incorporation of nano-llers such as piezoelectric lead zirconate titanate, 127 barium titanate, 128 layered silicates 129,130 and CNCs. 126 Cellulose is classied as natural piezoelectric material and its piezoelectric response have been studied in the last years, becoming a suitable material for energy harvesting device as well as storage application. The shear piezoelectricity of cellulose-based biopolymers such as wood, amylase, chitin, and starch can be comparable to that of quartz crystal.…”
Section: Piezoelectricity As Potential Emerging Application Of Pasmentioning
confidence: 99%
“…Aer comparing these results with PVDF-based sensor devices, the authors suggested CNF-based materials as a suitable precursor material for disposable piezoelectric sensors, actuators and energy generators with potential applications in the elds of electronics, sensors, and biomedical diagnostics. 103 More recently, F. Ram et al 126 reported the fabrication of a exible piezoelectric energy harvester based on PA11 and CNCs by a solution casting process. They showed for the rst time in literature the possibility to enhance the electroactive g phase in PA11 using CNCs, resulting in the increase of the piezoelectric performance of the device (Fig.…”
Section: Piezoelectricity As Potential Emerging Application Of Pasmentioning
confidence: 99%
See 1 more Smart Citation
“…The ability to enhance the piezoelectric coefficients of cellulose at the nanoscale has led to further interest in incorporating nanocellulose into both electroactive and conventional polymers for application in PENGs. [ 86,87 ] For instance, the PVDF which is commonly used electroactive polymer, presents the high piezoelectric, ferroelectric, and pyroelectric characteristics, when high β and γ phase crystallites present in the matrix. [ 88 ] The β phase is typically enhanced by tuning the processing conditions, copolymerization and incorporation of inorganic nanoparticles.…”
Section: Piezoelectricity and Applicationsmentioning
confidence: 99%